Building an Active and Happy Lifestyle in the Village - Dahri, Nur Wahyunianti; Aqil, Muhammad; Damayanti, Afriya; Anwar, Syaiful; Hajira, Hajira; Haq, Andi Rafli; Imran, Imran (Joong-Ki : Jurnal Pengabdian Masyarakat, 2025)
Cheerful healthy gymnastics is a series of gymnastic movements that aim to maintain and improve physical fitness with fun music accompaniment to burn enthusiasm. This activity aims to gain health and physical fitness. A fit person means that the person has dynamic health that can support physical or psychological activities. Meanwhile, one's fitness can have a good influence on one's performance which will affect productivity in living everyday life. Physical fitness is the body's ability to carry out daily activities without feeling excessive fatigue so that it can live a productive life because it has enough energy to carry out physical activities smoothly. Through this community service activity, KKN students of Universitas Muhammadiyah Mamuju invited a members of the Family Welfare Development (PKK) in Karama village, Tinambung Subdistrict, to do cheerful healthy gymnastics activities regularly in the morning every week on Sundays. In addition to being beneficial for health, this exercise is also useful for improving mood (cheerfulness), making sleep soundly and can control weight.